Anti-cracking agent composition and application thereof
By optimizing the preparation process of 1,3-butanediol, controlling the impurity content in its preparation, an anti-cracking agent composition for lithium batteries was prepared, which solved the problems of cracking and unstable performance of graphite negative electrode of lithium batteries, and significantly improved the Charging and discharging performance of lithium batteries.
Patent Information
- Application Number
- CN202411548403.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2024-12-17
AI Technical Summary
The graphite negative electrode of existing lithium batteries is prone to cracking during the preparation process, resulting in unstable battery discharge performance. The presence of by-products in 1,3-butanediol products affects the performance of lithium batteries. The existing methods fail to effectively control these impurities on the battery. Influence.
By optimizing the preparation process of 1,3-butanediol, and controlling that when its relative retention time is 1.0, the content of the corresponding components of the peaks within the range of 1.1-1.3 is within the range of 1-1000ppm, a kind of anti-cracking prevention is prepared. Agent composition is used for the negative electrode of lithium battery to avoid adverse effects of impurities on battery performance.
It effectively reduces the cracking of the negative electrode of the lithium battery, and controls the impurity content below 1000ppm to avoid its adverse effects on the charging and discharging performance of the lithium battery to the greatest extent, and improves the overall performance of the battery.
Smart Images

Figure BDA0005114420940000131 
Figure BDA0005114420940000132 
Figure BDA0005114420940000151
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries, and in particular relates to an anti-cracking agent composition and application thereof. Background Art
[0002] 1,3-Butanediol is a colorless and odorless liquid. Its unique diol structure gives it excellent chemical properties. It is widely used in daily chemicals, synthetic resins and other industries. In recent years, it has been found to have good application characteristics in lithium battery negative electrodes, which has expanded its market while putting forward higher requirements for its preparation optimization and product quality.
[0003] In the traditional process of preparing graphite negative electrodes for lithium batteries, the prepared graphite curled film is very prone to cracking, which leads to unstable discharge performance of the battery. If the graphite powder is dispersed in a solvent containing 1,3-butanediol during the preparation of the graphite curled film, the graphite curled film obtained after the solvent evaporates will have greatly reduced cracking. The appropriate chemical polarity of 1,3-butanediol can reduce the cracking of graphite.
[0004] However, when the 1,3-butanediol product prepared by the existing manufacturing method is used as an anti-cracking agent, although the graphite curling film will not crack, its discharge properties are still unstable. Although the mechanism is not clear, it is believed to be related to the by-products contained in the 1,3-butanediol product.
[0005] In order to solve this problem, it is necessary to optimize the preparation process and purification process of 1,3-butanediol products to obtain highly purified 1,3-butanediol products, and the specific impurities must be controlled within a certain content range.
[0006] Patent documents JP6890708B2 and JP2021042214A disclose a method for controlling odor-producing impurities in 1,3-butanediol products, but have not yet proposed impurities that affect lithium battery discharge in the application of lithium battery negative electrode anti-cracking agents and a method for controlling the impurities.
[0007] In summary, in the field of using 1,3-butanediol products produced by existing processes as anti-cracking agents for negative electrodes of lithium batteries, it is urgent to identify the relevant impurities that affect the discharge of lithium batteries, and it is urgent to further study the control methods of these impurities. Summary of the invention
[0008] In order to solve the above technical problems, the present invention proposes an anti-cracking agent composition and its application. In the anti-cracking agent composition, when the relative retention time of 1,3-butanediol is set to 1.0, the content of the component corresponding to the peak appearing in the relative retention time range of 1.1-1.3 is controlled within the range of 1-1000ppm, then such impurities remaining in the negative electrode prepared from the anti-cracking agent composition will not have an adverse effect on the overall charging and discharging performance of the lithium battery.
[0009] In order to achieve the above object, the present invention provides the following technical solutions:
[0010] In a first aspect, a 1,3-butanediol-based anti-cracking agent composition is provided, the anti-cracking agent composition comprising: 1,3-butanediol as component I, and component II corresponding to a peak appearing in the range of relative retention time of 1.1-1.3 when the relative retention time of 1,3-butanediol is set to 1.0 under gas chromatography analysis;
[0011] In the anti-cracking agent composition, the content of component II corresponding to the peak appearing in the relative retention time range of 1.1-1.3 is 1-1000ppm (for example, 2ppm, 4ppm, 5ppm, 8ppm, 10ppm, 20ppm, 30ppm, 40ppm, 50ppm, 80ppm, 90ppm, 120ppm, 150ppm, 300ppm, 400ppm, 500ppm, 600ppm, 800ppm, 900ppm), preferably 1-200ppm, more preferably 1-100ppm (or it can be expressed as: the area ratio of component II corresponding to the peak appearing in the relative retention time range of 1.1-1.3 is 1-1000ppm); the balance is 1,3-butanediol.
[0012] According to the anti-cracking agent composition provided by the present invention, in some embodiments, when the relative retention time of 1,3-butanediol is set to 1.0 under gas chromatography analysis, the general structural formula of component II corresponding to the peak appearing in the range of relative retention time 1.1-1.3 is C6H 14 O2; its molecular weight is in the range of 118-119 g / mol.
[0013] In some embodiments, the peak appearing in the relative retention time range of 1.1-1.3 corresponds to component II which is 3-methyl-2,4-pentanediol and / or its isomers.
[0014] According to the anti-cracking agent composition provided by the present invention, in some embodiments, the conditions for the gas chromatography analysis include:
[0015] Chromatographic column: capillary column, column material: fused quartz;
[0016] Model / stationary phase: Model is DB-5, stationary phase is (5% phenyl)-methylpolysiloxane;
[0017] Column length: 30m;
[0018] Column inner diameter: 0.32mm;
[0019] Liquid film thickness: 0.25μm;
[0020] Column temperature: initial temperature 50℃, maintained for 2 min, then increased to 80℃ at 5℃ / min, then increased to 280℃ at 15℃ / min and maintained for 15 min;
[0021] Carrier gas: nitrogen;
[0022] Carrier gas flow rate: 1.5 mL / min (constant flow mode);
[0023] Vaporization chamber temperature: 270℃;
[0024] Detector temperature: 280°C;
[0025] Injection volume: 1.0 μL;
[0026] Split ratio: 10:1;
[0027] Air flow rate: 400mL / min;
[0028] Hydrogen gas flow rate: 30mL / min;
[0029] Make-up gas flow rate: 25 mL / min;
[0030] Injection sample: 1 uL of 10% by weight sample in acetonitrile.
[0031] In a second aspect, a use of the anti-cracking agent composition as described above in a negative electrode sheet of a lithium battery is provided.
[0032] According to the application provided by the present invention, in some embodiments, the negative electrode sheet of the lithium battery is prepared by a negative electrode slurry;
[0033] The negative electrode slurry comprises: a negative electrode active material, a conductive agent, a binder and the anti-cracking agent composition.
[0034] In some embodiments, the method for preparing the negative electrode slurry comprises the following steps:
[0035] (1) preparing an electrode dispersion: mixing water and the anti-cracking agent composition evenly to prepare an anti-cracking agent aqueous solution; the concentration of the anti-cracking agent aqueous solution may be 0.5 wt%-3 wt% (e.g., 0.6 wt%, 1 wt%, 1.5 wt%, 2 wt%, 2.5 wt%, 2.8 wt%);
[0036] (2) preparing an aqueous binder solution: uniformly mixing the anti-cracking agent aqueous solution obtained above with the binder to prepare an aqueous binder solution;
[0037] (3) Preparing slurry: The negative electrode active material, the conductive agent and the aqueous binder solution obtained above are mixed to form a uniform negative electrode slurry.
[0038] Herein, the negative electrode slurry includes dry components, which may be a negative electrode active material, a conductive agent, a binder, and an anti-cracking agent composition.
[0039] Herein, the viscosity of the negative electrode slurry is 3000-15000mP·s (for example, 3500mP·s, 4000mP·s, 5000mP·s, 6000mP·s, 7000mP·s, 8000mP·s, 10000mP·s, 11000mP·s, 12000mP·s, 14000mP·s, 14500mP·s); and the solid content of the negative electrode slurry is 30-70wt% (for example, 35wt%, 40wt%, 45wt%, 50wt%, 55wt%, 60wt%, 65wt%).
[0040] In some embodiments, in the negative electrode slurry, the amount of the anti-cracking agent composition is 0.1-2wt% (for example, 0.2wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.8wt%, 1wt%, 1.5wt%, 1.8wt%) based on the total weight of all components.
[0041] In some embodiments, in the negative electrode slurry, based on the total weight of each component:
[0042] The amount of the negative electrode active material is 75-98wt% (for example, 76wt%, 80wt%, 85wt%, 90wt%, 95wt%, 96wt%);
[0043] The amount of the conductive agent is 1-20wt% (for example, 2wt%, 4wt%, 5wt%, 6wt%, 10wt%, 12wt%, 15wt%, 18wt%),
[0044] The amount of the binder used is 1-10wt% (for example, 2wt%, 4wt%, 5wt%, 6wt%, 8wt%, 9wt%).
[0045] In some embodiments, the negative electrode active material is selected from one or more of graphite, silicon, silicon oxygen and silicon carbon.
[0046] In some embodiments, the conductive agent is selected from one or more of carbon black, carbon nanotubes, graphene and carbon fibers.
[0047] In some embodiments, the binder is selected from one or more of sodium carboxymethyl cellulose (CMC), styrene-butadiene latex, acrylamide binders, acrylonitrile binders, polyvinyl alcohol and sodium alginate binders.
[0048] Herein, the operation process of preparing a lithium battery according to the provided negative electrode plate can be a conventional choice in the art and will not be described in detail here.
[0049] In the present invention, the anti-cracking agent composition as described above can be prepared by a variety of methods. Those skilled in the art should understand that the following preparation method is only an exemplary description of the source of the anti-cracking agent composition having the above characteristics of the present invention, but does not constitute any limitation.
[0050] For example, in some embodiments, the method for preparing the anti-cracking agent composition as described above comprises the following steps:
[0051] (1) acetaldehyde condensation: in the presence of an alkaline catalyst, acetaldehyde is subjected to a condensation reaction to prepare a reaction mixture containing 3-hydroxybutyraldehyde, and then unreacted acetaldehyde is removed to obtain a hydrogenation raw material liquid;
[0052] The condensation reaction process can use a tank reactor or an external circulation reactor, and the mixing effect is strictly controlled, preferably a tank reactor;
[0053] The linear speed of the agitator for stirring is controlled at 3.36-12.67 m / s (for example, 3.5 m / s, 4.0 m / s, 5.0 m / s, 6.0 m / s, 8.0 m / s, 9.0 m / s, 10.0 m / s, 12.0 m / s), preferably 6.18-9.62 m / s; the reaction is carried out at this stirring linear speed, the reaction speed is moderate, the mixing effect is good, and the impurity content in the obtained product can be effectively controlled; when the stirring speed is lower than 3.36 m / s, the material is not stirred sufficiently, and when the stirring speed is higher than 12.67 m / s, the energy consumption rises sharply and the reaction temperature rises, which will cause more impurities to be generated; if an external circulation reactor is used, the same mixing effect as the above-mentioned kettle reactor should be achieved;
[0054] (2) hydrogenation reaction: in the presence of a hydrogenation catalyst, subjecting the hydrogenation raw material liquid obtained in step (1) to a hydrolysis hydrogenation reaction, so that the 3-hydroxybutyraldehyde intermediate generated by the above reaction is hydrogenated to generate a reaction liquid containing 1,3-butanediol;
[0055] (3) Distillation separation: The reaction liquid containing 1,3-butanediol obtained in step (2) is subjected to distillation separation to obtain an anti-cracking agent composition.
[0056] According to the above method, in the prepared anti-cracking agent composition, when the relative retention time of 1,3-butanediol is set to 1.0, the content of component II (residual impurities) corresponding to the peak appearing in the relative retention time range of 1.1-1.3 is in the range of 1-1000 ppm.
[0057] According to the method described above, the alkaline catalyst in step (1) may include but is not limited to one or more of sodium hydroxide, potassium hydroxide, lithium hydroxide, trimethylamine and triethylamine.
[0058] According to the method as described above, the reaction temperature of the condensation reaction in step (1) is 0-30°C (e.g., 2°C, 4°C, 5°C, 6°C, 8°C, 10°C, 12°C, 14°C, 15°C, 20°C, 22°C, 25°C, 28°C), preferably 5-15°C, and the reaction time can be 6-9h (e.g., 6.5h, 7h, 7.5h, 8h, 8.5h).
[0059] According to the above method, the condensation process is carried out using a tank reactor or an external circulation reactor, and the mixing effect is strictly controlled, preferably a tank reactor; by controlling the stirring linear speed of the stirrer to 3.36-12.67 m / s, preferably 6.18-9.62 m / s, under this condition, the reaction speed can be ensured to be moderate, and the total conversion rate of 3-hydroxybutyraldehyde in the obtained product is greater than 99.9%. If an external circulation reactor is used, the same mixing effect as the above-mentioned tank reactor should be achieved.
[0060] According to the method as described above, the hydrogenation catalyst used in step (2) can be one or more of Raney nickel, Raney cobalt, supported nickel and supported cobalt catalysts. The preparation process of the hydrogenation catalyst can be achieved by conventional operations in the art, which will not be repeated here. The content of each component in the hydrogenation catalyst can also be a conventional choice in the art. For example, the hydrogenation catalyst can also be obtained by commercially purchasing commercial products.
[0061] According to the method described above, the hydrogenation reaction in step (2) can be carried out using a fixed bed reactor or a tank reactor.
[0062] According to the method as described above, the process conditions of the hydrogenation reaction in step (2) include: the reaction temperature range can be 80-180°C (for example, 90°C, 100°C, 120°C, 135°C, 145°C), preferably 100-160°C, more preferably 120-140°C, the pressure range can be 2-20MPa (for example, 3MPa, 4MPa, 4.5MPa, 5.5MPa, 6.5MPa, 7MPa, 8MPa, 10MPa, 15MPa, 18MPa), preferably 3-12MPa (gauge pressure); the reaction space velocity can be 0.05-0.5h -1 (For example, 0.06h -1 , 0.1h -1 、0.2h -1 , 0.25h -1 、0.3h -1 , 0.35h -1 、0.4h -1 , 0.45h -1 ).
[0063] According to the method described above, the distillation separation process in step (3) can be performed by intermittent distillation or continuous distillation. The equipment and distillation process conditions used in the distillation separation process can be conventionally selected in the art. For example, the distillation equipment can be a packed tower or a plate tower, the number of plates can be, for example, 10-20 (e.g., 12, 14, 15, 18), the operating pressure can be, for example, 2-5 kPa (absolute pressure), and the fraction at 102-110° C. is collected by distillation to obtain an anti-cracking agent composition.
[0064] The inventors have found through repeated verification that one of the reasons why the 1,3-butanediol products prepared by the existing method will affect the discharge of lithium batteries is that the 1,3-butanediol products will inevitably contain a certain amount of higher carbon chain chemicals (as impurities), which are not easy to volatilize and have high chemical polarity. These impurities remaining in the negative electrode will affect the overall discharge performance of the lithium battery.
[0065] In order to solve this problem, the inventors have found through extensive research that in a 1,3-butanediol product (or an anti-cracking agent composition), when the relative retention time of 1,3-butanediol is set to 1.0, the content of component II (residual impurities) corresponding to the peak appearing in the relative retention time range of 1.1-1.3 is controlled within the range of 1-1000ppm, which can avoid the adverse effects of the residual impurities in the 1,3-butanediol product on the overall charging and discharging performance of the lithium battery to the greatest extent; this may be because: the residual amount of the impurity is controlled below 1000ppm, and the polarity accumulation caused by it is within a controllable range, which has little effect on the charging and discharging of the battery or even has no adverse effect. DETAILED DESCRIPTION
[0066] In order to understand the technical features and content of the present invention in detail, the preferred embodiments of the present invention will be described in more detail below. Although the preferred embodiments of the present invention are described in the embodiments, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments described herein. For those who do not specify specific conditions in the embodiments, they are carried out according to normal conditions or the conditions recommended by the manufacturer.
[0067] In the following examples and comparative examples, the sources of some reagents or raw materials used, if the manufacturer of the reagents or raw materials is not indicated, are conventional products that can be purchased from the market.
[0068] Preparation Example of Anti-cracking Agent Composition
[0069] The preparation steps of the anti-cracking agent composition are as follows:
[0070] (1) In a reactor, 50 g of a 1 wt % sodium hydroxide aqueous solution was added dropwise to 500 g of acetaldehyde stream (purity ≥ 99.5%) for 4 h. The condensation reaction temperature was controlled at 10-15° C. by a cold bath. After the addition was completed, the reaction was continued for 3 h. Then, acetic acid was added to the system for neutralization until the system was neutral. The condensation reaction was carried out under stirring, and the stirring linear speed of Examples 1-6 was carried out according to the conditions shown in Table 1.
[0071] Then, unreacted acetaldehyde in the system is removed by short-path evaporation and recovered to obtain a condensation liquid of 3-hydroxybutyraldehyde (i.e., hydrogenation raw material liquid);
[0072] (2) Raney nickel hydrogenation catalyst (Raney 6800, purchased from GRACE) was loaded into two hydrogenation fixed reactors connected in series, 50 mL of hydrogenation catalyst was loaded into each of the two hydrogenation fixed reactors, and the hydrogenation catalyst was activated with hydrogen at 2 MPa and 380° C. for 8 h, then cooled to the reaction temperature and adjusted to the reaction pressure;
[0073] Then, 1 weight percent ethanol was added to the condensed solution of 3-hydroxybutyraldehyde obtained in step (1) to dilute it to a concentration of 50 wt %, and the solution was continuously pumped into the hydrogenation fixed reactor at a reaction volume space velocity of 0.2 h -1 , the reaction pressure is 6MPa (gauge pressure), and the reaction temperature is 130°C;
[0074] (3) The reaction solution containing 1,3-butanediol obtained in step (2) is subjected to distillation separation under the following distillation conditions: the number of plates is 15 and the distillation pressure is 2.5 KPa (absolute pressure); the fraction at 106-107° C. is collected to obtain an anti-cracking agent composition product (the products obtained in Examples 1-6 are numbered as anti-cracking agent composition 1# to anti-cracking agent composition 6#).
[0075] Comparative Example of Preparation of Anti-cracking Agent Composition
[0076] The operation steps of the above embodiment were followed, except that: step (1) adopted different stirring linear speeds for condensation reaction, and the stirring linear speed conditions of comparative examples 1-3 are shown in Table 2; the remaining steps were the same as those of the embodiment (the products obtained in comparative examples 1-3 were numbered as anti-cracking agent composition 1'# to anti-cracking agent composition 3'#).
[0077] In order to evaluate the anti-cracking agent composition obtained in each embodiment and comparative example, gas chromatography was used for analysis, and the area ratio of 1,3-butanediol was read. If the relative retention time of 1,3-butanediol was set to 1.0, the area ratio of the component corresponding to the peak appearing in the relative retention time range of 1.1-1.3 was read; the conditions for gas chromatography analysis were:
[0078] Chromatographic column: capillary column, column material: fused quartz;
[0079] Model / stationary phase: Model is DB-5, stationary phase is (5% phenyl)-methylpolysiloxane;
[0080] Column length: 30m;
[0081] Column inner diameter: 0.32mm;
[0082] Liquid film thickness: 0.25μm;
[0083] Column temperature: initial temperature 50℃, maintained for 2 min, then increased to 80℃ at 5℃ / min, then increased to 280℃ at 15℃ / min and maintained for 15 min;
[0084] Carrier gas: nitrogen;
[0085] Carrier gas flow rate: 1.5 mL / min (constant flow mode);
[0086] Vaporization chamber temperature: 270℃;
[0087] Detector temperature: 280°C;
[0088] Injection volume: 1.0 μL;
[0089] Split ratio: 10:1;
[0090] Air flow rate: 400mL / min;
[0091] Hydrogen gas flow rate: 30mL / min;
[0092] Make-up gas flow rate: 25 mL / min;
[0093] Injection sample: 1 uL of 10% by weight sample in acetonitrile.
[0094] In the anti-cracking agent composition products prepared in each embodiment and comparative example, if the relative retention time of 1,3-butanediol is set to 1.0, the peak appearing in the relative retention time range of 1.1-1.3 corresponds to component II which is 3-methyl-2,4-pentanediol and / or its isomers.
[0095] After the anti-cracking agent compositions 1# to 6# prepared in each example were analyzed by gas chromatography, the area ratio of component II corresponding to the peaks appearing in the relative retention time range of 1.1-1.3 is shown in Table 1;
[0096] After the anti-cracking agent compositions 1'# to 3'# prepared in each comparative example were analyzed by gas chromatography, the area ratios of component II corresponding to the peaks appearing in the relative retention time range of 1.1-1.3 are shown in Table 2.
[0097] Table 1 Partial process parameters and test results of Examples 1-6
[0098]
[0099] Table 2 Partial process parameters and test results of comparative examples 1-3
[0100]
[0101] Battery discharge performance evaluation
[0102] 1. Preparation process of lithium battery electrode (negative electrode) plate:
[0103] (1) The anti-cracking agent compositions prepared in Examples 1-6 and Comparative Examples 1-3 were dissolved in water respectively, and then sodium carboxymethyl cellulose as a binder was added thereto and mixed evenly, and then graphite as a negative electrode active material and conductive carbon black as a conductive agent were added thereto, and magnetic stirring was performed for 5-6 hours to mix them evenly to form each group of negative electrode slurries with appropriate viscosity and uniform composition, wherein the viscosity was 7000 mP·s and the solid content was 50 wt %; based on the total weight of each component being 100 wt %, the amounts of the negative electrode active material, the conductive agent, the binder and the anti-cracking agent composition were 80 wt %, 13 wt %, 6 wt % and 1 wt % respectively;
[0104] (2) Using a glass rod, the negative electrode slurries prepared above were evenly coated on the copper foil cleaned with anhydrous ethanol, and then transferred to an oven after being marked with serial numbers, and vacuum dried at 100° C. for 8 h to obtain the electrode-copper foils of each group;
[0105] (3) Each group of electrode-copper foil prepared above is placed in an oven at 100°C for drying, and then the dried electrode-copper foil is taken out and placed flat on a roller press, and the roller spacing and roller pressure are adjusted to compact the electrode sheet, and then several electrode sheets are cut out using a button cell slicer and stored in a vacuum drying oven.
[0106] 2. Battery assembly:
[0107] The battery is assembled in a glove box filled with inert gas. The assembly order is as follows: place the positive electrode shell, use tweezers to gently place the electrode sheets prepared as above in the center of the positive electrode shell, add 1-3 drops of electrolyte on top, cover with the diaphragm and add 1-3 drops of electrolyte again, then place the metal lithium sheet, steel sheet, gasket, and negative electrode shell in sequence, and finally seal the assembled battery with a button battery sealer, paying attention to wipe it clean to avoid leakage. The positive electrode shell used for assembling the battery is a CR2025 battery shell, the diaphragm is a polytetrafluoroethylene microporous diaphragm, and the electrolyte is a mixed solution of ethylene carbonate + dimethyl carbonate + ethyl methyl carbonate dissolved with lithium salt LiPF6.
[0108] 3. Battery charge and discharge performance test:
[0109] The charge and discharge cycle performance test mainly includes the sum of the cycle performance tests, using 0.2C constant current charge and discharge, the test conditions are room temperature (25°C), the voltage range is set to 0.01-3V, and the instrument used is LAND CT2001A multi-channel battery tester. The cyclic voltammetry test is used to test the change of discharge capacity during the battery cycle and determine the cycle stability of the battery to be tested. This experiment is to test the discharge capacity after 100 cycles. The test results are shown in Table 3.
[0110] Table 3 Battery performance test results
[0111]
[0112] According to the test results in Tables 1-3 above, it is found that in the anti-cracking agent composition products prepared in each comparative example, the area ratio of the component corresponding to the peak appearing in the relative retention time range of 1.1-1.3 is greater than 1000ppm, which will have a great adverse effect on the discharge capacity, charging capacity and cycle discharge capacity of the lithium battery prepared therefrom. In the anti-cracking agent composition products prepared in each embodiment of the present invention, the area ratio of the component corresponding to the peak appearing in the relative retention time range of 1.1-1.3 is less than 1000ppm, indicating that the content of impurities such as 3-methyl-2,4-pentanediol and / or its isomers in the anti-cracking agent composition products prepared in each embodiment is controlled within the range of 1-1000ppm. When the anti-cracking agent composition product with this feature is applied to lithium batteries, the discharge capacity, charging capacity and cycle discharge capacity are greatly improved.
[0113] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those skilled in the art without departing from the spirit of the present invention.
Claims
1. A 1,3-butanediol-based anti-cracking agent composition, It is characterized in that The anti-cracking agent composition comprises: 1,3-butanediol as component I, and component II corresponding to a peak appearing in the range of relative retention time of 1.1-1.3 when the relative retention time of 1,3-butanediol is set to 1.0 under gas chromatography analysis; In the anti-cracking agent composition, the content of component II corresponding to the peak appearing in the relative retention time range of 1.1-1.3 is 1-1000 ppm, preferably 1-200 ppm, more preferably 1-100 ppm; the balance is 1,3-butanediol.
2. The anti-cracking agent composition according to claim 1, It is characterized in that When the relative retention time of 1,3-butanediol is set to 1.0 under gas chromatography analysis, the structural formula of component II corresponding to the peak in the relative retention time range of 1.1-1.3 is C 6 H 14 O 2 .
3. The anti-cracking agent composition according to claim 2, It is characterized in that The component II corresponding to the peak appearing in the relative retention time range of 1.1-1.3 is 3-methyl-2,4-pentanediol and / or its isomers.
4. The anti-cracking agent composition according to any one of claims 1 to 3, It is characterized in that The conditions for the gas chromatography analysis include: Chromatographic column: capillary column, column material: fused quartz; Model / stationary phase: Model is DB-5, stationary phase is (5% phenyl)-methylpolysiloxane; Column length: 30m; Column inner diameter: 0.32mm; Liquid film thickness: 0.25μm; Column temperature: initial temperature 50℃, maintained for 2 min, then increased to 80℃ at 5℃ / min, then increased to 280℃ at 15℃ / min and maintained for 15 min; Carrier gas: nitrogen; Carrier gas flow rate: 1.5 mL / min (constant flow mode); Vaporization chamber temperature: 270℃; Detector temperature: 280°C; Injection volume: 1.0 μL; Split ratio: 10:1; Air flow rate: 400mL / min; Hydrogen gas flow rate: 30mL / min; Make-up gas flow rate: 25 mL / min; Injection sample: 1 μL of 10% by weight sample in acetonitrile.
5. Use of the anti-cracking agent composition according to any one of claims 1 to 4 in a negative electrode sheet of a lithium battery.
6. The use according to claim 5, It is characterized in that The negative electrode sheet of the lithium battery is prepared by negative electrode slurry; The negative electrode slurry comprises: a negative electrode active material, a conductive agent, a binder and the anti-cracking agent composition.
7. The use according to claim 6, It is characterized in that The method for preparing the negative electrode slurry comprises the following steps: (1) preparing an electrode dispersion: uniformly mixing water and the anti-cracking agent composition to prepare an anti-cracking agent aqueous solution; (2) preparing an aqueous binder solution: uniformly mixing the anti-cracking agent aqueous solution obtained above with the binder to prepare an aqueous binder solution; (3) Preparing slurry: The negative electrode active material, the conductive agent and the aqueous binder solution obtained above are mixed to form a uniform negative electrode slurry.
8. The use according to claim 6 or 7, It is characterized in that In the negative electrode slurry, the amount of the anti-cracking agent composition is 0.1-2 wt % based on the total weight of each component.
9. The use according to any one of claims 6 to 8, It is characterized in that In the negative electrode slurry, based on the total weight of each component: The amount of the negative electrode active material is 75-98wt%; The amount of the conductive agent is 1-20wt%, The amount of the binder is 1-10 wt %.
10. The use according to any one of claims 6 to 9, It is characterized in that The negative electrode active material is selected from one or more of graphite, silicon, silicon oxygen and silicon carbon; The conductive agent is selected from one or more of carbon black, carbon nanotubes, graphene and carbon fiber; The binder is selected from one or more of sodium carboxymethyl cellulose, styrene-butadiene latex, acrylamide binder, acrylonitrile binder, polyvinyl alcohol and sodium alginate binder.
Citation Information
Patent Citations
1,3-butylene glycol product
JP2021042214A
1,3-butylene glycol products
JP6890708B2
